(3GdCOhjI GdeaQOI GdJi jaYd HNhGUgG aj GdSehes - (3jYbhH Hf ESMGb Hf GdUHGM GdcfOj, CHh jhSa,J (B260 (3g` s ((3eMeO Hf bWH GdWHjH s)
(3ChdgG (B:s
(3QSGdI jYbhH Hf ESMGb GdcfOi ai GdCOhjI GdeaQOI GdQaJ GdUGai jfaY ef GdSehe GdbGJdI hLejY dPY GdOhGH s
(3BNQgG (B:s
(3EPG cGf GdhLY TOjOkG hGdVQHGf eaQWkG dG jbQH Gdejd hGdPQhQ hdG GdOhGA GdMGO , EdjgG dcf jbWQ OhGA edjf eScf hdhGgH GdYbd GdMeO HdGfgGjI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B513 - (3U(B516s
(3GfXQg eY GdeQTO ddQGRi (B" 730"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B244s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B10 s
(3eUOQ GbJfGA GdCUd (B:s
(3ThGQi edi (B(1568) s
Keywords: (3GdWHs